2021
DOI: 10.1371/journal.pbio.3001487
|View full text |Cite
|
Sign up to set email alerts
|

Locus coeruleus neurons encode the subjective difficulty of triggering and executing actions

Abstract: The brain stem noradrenergic nucleus locus coeruleus (LC) is involved in various costly processes: arousal, stress, and attention. Recent work has pointed toward an implication in physical effort, and indirect evidence suggests that the LC could be also involved in cognitive effort. To assess the dynamic relation between LC activity, effort production, and difficulty, we recorded the activity of 193 LC single units in 5 monkeys performing 2 discounting tasks (a delay discounting task and a force discounting ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 93 publications
1
21
0
Order By: Relevance
“…Early electrophysiology studies in rats (5,8) and monkeys (9) noted inhibition of LC neurons during liquid consumption of sucrose or juice. In contrast, LC neurons are endogenously activated by cues predicting reward availability, and this activation is modulated by reward size and effort (10)(11)(12). Whether these endogenous LC responses play a causal role in the regulation of feeding behaviors remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Early electrophysiology studies in rats (5,8) and monkeys (9) noted inhibition of LC neurons during liquid consumption of sucrose or juice. In contrast, LC neurons are endogenously activated by cues predicting reward availability, and this activation is modulated by reward size and effort (10)(11)(12). Whether these endogenous LC responses play a causal role in the regulation of feeding behaviors remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As for neural implementation, phasic locus coeruleus (LC) activity is known to transmit feedforward information to the SEF via ascending projections to the prefrontal cortex (PFC), providing a plausible pathway for such a bottom-up influence. Recent work has shown that LC neurons can reflect both cognitive and physical efforts with a subsecond precision [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this new study, Bornert and Bouret [ 4 ] highlight important properties of LC neurons compatible with the notion of subjective difficulty to overcome both physical and cognitive challenges.…”
mentioning
confidence: 82%